Effects of Rural-Urban Migration on Children Who Accompany Adults to Madina - Adisenu, S.S. (University of Ghana, 2017)
Studies on the effects of rural-urban migration on children who accompany adults from the rural areas to the urban centres have been under-researched in the world, Africa and particularly in Ghana. The increasing number of adult migrants with accompanying children from the rural areas to the urban centres has contributed to the influx of children in the urban centres in Ghana. It was for this reason that the study sought to investigate the effects of rural-urban migration on children who accompany adults to Madina, Accra. The objectives of the study were: (1) to describe the socio-demographic characteristic of the children and their parents/relatives/guardian, (2) to examine the effects of rural-urban migration on the educational performance of these children, and (3) to investigate some possible changes in lifestyle since they accompanied their parents to Madina, Accra. The study adopted quantitative and qualitative approaches to gather the data. A simple random sampling method was employed to sample two schools each from two clusters, out of which one hundred (100) children between the ages of 12-17 were selected for the survey. In-depth interviews were also conducted for seven adults which were made up of four males and three females. The children were used as nodes in getting access to the parents for the interview in their various locations. The findings of this study shows that in the Ghanaian context rural-urban migration improve the educational performance of accompanying children in Madina. Again, on the lifestyle changes of the children, it was discovered that rural-urban migration affected the lifestyles of some children negatively whiles others were positively affected. However, the negative changes outweighed the positives. In view of these, it is recommended that schools should organize interactive sessions where school authorities, teachers, parents, relatives and guardian discuss the needs and challenges which these accompanying children may encounter and how they can collaborate to help sustain their performance. School authorities should make the effort to identify the rural-urban University of Ghana http://ugspace.ug.edu.gh v accompanying children and partner with their parents or relatives in order to provide the needed support for these children who may have challenges with their living arrangement, health care and are also exposed to some lifestyles. Parents and guardians of accompanying children should keep a closer eye on the children to protect them from engaging in some risky lifestyles, for instance stealing, smoking and drinking. University of Ghana http://ugspace.ug.edu.gh
Keywords: Effects of Rural-Urban Migration; Children Who Accompany Adults to Madina; educational performance of these children